First In Vitro-In Silico Analysis for the Determination of Antimicrobial and Antioxidant Properties of 2-(4-Methoxyphenylamino)-2-oxoethyl Methacrylate and p-Acetamide - Temuz, Mehmet Mursit; Cankaya, Nevin; Korcan, Safiye Elif; Azarkan, Serap Yalcin; Kahraman, Tugba (Amer Chemical Soc, 2024)
The antibacterial, antifungal, and antioxidant activities of 2-chloro-N-(4-methoxyphenyl)acetamide (p-acetamide) and 2-(4-methoxyphenylamino)-2-oxoethyl methacrylate (MPAEMA) were investigated by in vitro experiments and in silico analyses. MPAEMA has an antibacterial effect only against Gram-positive Staphylococcus aureus. It was determined that this did not affect any other bacteria and Candida glabrata yeast. On the other hand, p-acetamide showed antimicrobial activity against S. aureus ATCC 25923, C. glabrata ATCC 90030, Bacillus subtilis NRRL 744, Enterococcus faecalis ATCC 551289, Escherichia coli ATCC 25922, Klebsiella pneumoniae NRLLB4420, Pseudomonas aeruginosa ATCC 27853, and Listeria monocytogenes ATCC 1911. p-Acetamide showed the greatest antifungal effect by inhibiting the colony growth of Trichoderma longibrachiatum (98%). This was followed by Mucor plumbeus with 83% and Fusarium solani with 21%. MPAEMA inhibited colony growth of T. longibrachiatum by 95% and that of M. plumbeus by 91%. Also, p-acetamide and MPAEMA had a scavenging effect on free radicals. According to results of the in silico analysis, the antimicrobial effect of these compounds is due to their effect on DNA ligase. Based on drug-likeness analysis, they were found to be consistent with the Lipinski, Veber, or Ghose rule. p-Acetamide and MPAEMA may be used as drugs.